Analisis perilaku “baku bawa” pada pasangan ibu hamil dengan HIV/AIDS di Papua - Pratami, Yustika Rahmawati; Vitania, Wiwit; Hasnia, Hasnia; Astutik, Eftyaningrum Dwi Wahyu; Handayani, Endah Purwanti; Palino, Keryn Amanda (Holistik Jurnal Kesehatan, 2026)
Background: The shift in HIV test results in pregnant women from negative to positive during pregnancy indicates a gap in the implementation of the PMTCT program, primarily because HIV testing is generally only performed once on pregnant women and does not optimally involve partners. The practice of "baku bawa," or living together without formal marriage, which is quite common in Papua, has the potential to increase risky sexual behavior. Therefore, this study is important as a basis for strengthening PMTCT policies to prevent delays in addressing vertical HIV transmission. Purpose: To describe the "baku bawa" behavior of couples of pregnant women living with HIV/AIDS. Method: This mixed-methods study used a quantitative descriptive design with a cross-sectional approach and a qualitative descriptive design with in-depth interviews and focus group discussions (FGDs). Results: There were 14 categories of quantitative analysis, and five themes were identified in the in-depth interviews in the qualitative study related to the behavior of couples with "baku bawa." Conclusion: The behavior of "baku bawa," or living together without formal marriage, among couples with pregnant women is associated with an increased risk of HIV transmission. This confirms that sexual behavior and relationship dynamics in the practice of "baku bawa" require attention in efforts to prevent HIV transmission, particularly in strengthening PMTCT programs through educational approaches, partner screening, and promotion of safe sexual behavior.   Keywords: Baku Bawa; Couples; HIV Testing; Pregnant Women; Sexual Behavior.   Pendahuluan: Perubahan hasil tes HIV pada ibu hamil dari negatif menjadi positif selama masa kehamilan menunjukkan adanya celah dalam pelaksanaan program pencegahan penularan HIV dari ibu ke anak (PPIA), terutama karena tes HIV umumnya hanya dilakukan sekali pada ibu hamil dan belum melibatkan pasangan secara optimal. Praktik “baku bawa”, yaitu hidup bersama tanpa pernikahan formal yang cukup umum di Papua, berpotensi meningkatkan perilaku seksual berisiko, sehingga penelitian ini penting sebagai dasar penguatan kebijakan PPIA, guna mencegah keterlambatan penanganan penularan HIV secara vertikal. Tujuan: Untuk mendeskripsikan perilaku “baku bawa” pada pasangan ibu hamil dengan HIV/AIDS. Metode: Penelitian mix method dengan desain deskriptif kuantitatif dengan pendekatan cross sectional dan deskriptif kualitatif dengan pendekatan indepth interview dan FGD. Hasil: Terdapat 14 kategori analisis kuantitatif dan dan pada wawancara mendalam pada penelitian kualitatif terkait perilaku pasangan “baku bawa” ditemukan 5 tema. Simpulan: Perilaku “baku bawa” atau hidup bersama tanpa ikatan pernikahan formal pada pasangan ibu hamil memiliki keterkaitan dengan peningkatan risiko penularan HIV. Hal ini menegaskan, bahwa faktor perilaku seksual dan dinamika hubungan pasangan dalam praktik “baku bawa” perlu menjadi perhatian dalam upaya pencegahan penularan HIV, khususnya dalam penguatan program PPIA melalui pendekatan edukasi, skrining pasangan, dan promosi perilaku seksual yang aman.   Kata Kunci: Baku Bawa; Ibu Hamil; Pasangan; Perilaku Seks; Tes HIV.